Title: Confronting Harassment in Healthcare Workplaces: An Experience Report with NASSA Workers (CIPEEX, 2025)
AbstractThis experience report describes the implementation of an operative group on workplaceharassment with workers from NASSA (Occupational Health Support Center of Anápolis),developed by Group 4 of the PET-Health Equity Program. The objective was to promotecritical reflection on different forms of harassment — moral, sexual, virtual, school-related,and discriminatory — through participatory activities that stimulated dialogue, the sharing ofexperiences, and the construction of collective coping strategies. The method followed astructured script in five stages: welcoming, integration activity, conceptual presentation withcontextualized examples, discussion circle guided by key questions, and presentation ofinstitutional channels for reporting and prevention. A preliminary rehearsal with the PET-Health team allowed adjustments in clarity, timing, and appropriateness of the conduction.The results indicated increased awareness of the impacts of harassment on personal andprofessional life, strengthening of collective dialogue spaces, and appreciation ofinstitutional equity policies. It is concluded that the operative group constituted a mobilizingpractice, with the potential to empower workers and contribute to critical training inoccupational health and health education.Keywords: Moral Harassment; Sexual Harassment; Occupational Health; Health Equity;Health Education
Keywords: Moral Harassment; Sexual Harassment; Occupational Health; Health Equity; Health Education